Soil Aggregate Dynamics and Plant Community Response after Biosolids Application in a Semiarid Grassland. Issue 5 (1st September 2016) - Wallace, Brian M.; Krzic, Maja; Newman, Reg F.; Forge, Tom A.; Broersma, Klaas; Neilsen, Gerry
Abstract : Biosolids may improve the ecological function of degraded semiarid grasslands, but an understanding of the plant community is essential. An experiment was established in 2001 to determine the effects of a single surface application of biosolids on soil aggregate stability and the composition of the plant community in a semiarid grassland in British Columbia, Canada. Four treatments were evaluated: (i) surface biosolids application at 20 (Bio‐20) and (ii) 60 Mg ha 1 (Bio‐60), (iii) mineral fertilizer, and (iv) a control. All treatments were replicated in four blocks. Soil was sampled during the spring (May), summer (June–July), and fall (October) in 2005, 2006, and 2009; the plant community was assessed in 2009. The greatest increases in size of stable aggregates relative to the control were in the spring and summer, which coincided with a 1.6‐ to 2.1‐fold increase in the spring concentration of N within stable aggregates when biosolids were applied at 20 and 60 Mg ha 1, respectively. Nitrogen concentrations from the Bio‐60 treatment were not different from the control, but the Bio‐20 treatment had 42% greater N than all other treatments during summer. Biosolids application in this ecosystem did not increase perennial forage grass species relative to the control, and when biosolids were applied at a rate of 60 Mg ha 1 there was a 75% reduction in the perennial forage plant species. The application of biosolids to native grasslands in semiarid environments should be done cautiously, especially when winter annual plant species (e.g., cheatgrass [ Bromus tectorum L.]) are present before application. Core Ideas: Increased size and stability of soil aggregates 8 yr after a single biosolids application. Evidence of a large nutrient flux early in the growing season 8 yr after biosolids application. Biosolids decreased the cover of perennial grasses while increasing winter annuals. The recovery of degraded grasslands is a slow process in semiarid environments.